Integrating Cabbage Waste into Pelletized Rabbit Feed to Optimize Calcium and Phosphorus Content - Sudarman; Nurul Amin (Edupedia Publisher, 2025)
The utilization of agricultural waste as livestock feed ingredients is an important strategy to enhance sustainability in integrated farming systems. This study evaluated the effect of cabbage waste inclusion in pelletized rabbit feed on calcium and phosphorus content. A completely randomized design was applied using four dietary treatments containing 0%, 5%, 10%, and 15% cabbage waste. Mineral concentrations were analyzed to assess nutritional responses. The results demonstrated that cabbage waste significantly affected mineral composition of the pellets. Calcium content increased at inclusion levels of 5–15%, with the highest value observed at 15%, while phosphorus content showed a balanced but significant response across treatments. These findings indicate that moderate inclusion levels optimize mineral availability without compromising nutrient balance. This study demonstrates that cabbage waste can be effectively valorized as a functional feed ingredient, contributing to circular resource use. Overall, the integration of cabbage waste into pelletized rabbit feed supports nutritionally adequate, resource-efficient, and sustainable livestock production systems.